Pelajaran dari Aktivisme Digital KawalCOVID19 dalam Melawan Infodemic pada Masa Pandemi COVID-19 di Indonesia - Agne Yasa; Rahayu (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2023)
Infodemic and inadequate government public communications have encouraged the birth of digital activism KawalCOVID19 as a source of information about COVID-19. This article aims to identify practices, challenges, and forms of KawalCOVID19 digital activism in fighting the infodemic in Indonesia. This study uses the concept of infodemic, digital activism, and New Social Movement theory with a single case study qualitative method. This study found that KawalCOVID19 fights the infodemic with strategies for collecting, verifying, and analyzing COVID-19 data at the regional and central levels; providing informational, educational, and verification content about COVID-19; disseminating information on the website and social media to the public, and advocating government policy; and collaborating to extend the reach. KawalCOVID19 faces challenges from technological, interactional, personal, and policy perspectives. KawalCOVID19 is a form of data activism in the category of digital gladiatorial activities. Furthermore, digital activism continues to grow and presents opportunities for theoretical and empirical studies with different contexts and different activism actors and also analysis of the reception of activism. Â